2011
DOI: 10.1097/mnm.0b013e32834754f1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinicopathological factors and fluorine-18-fluorodeoxyglucose uptake in patients with papillary thyroid cancer

Abstract: F-FDG uptake in PTC may be determined by GLUT-3 and GLUT-4 expressions and may be related to tumor size and lymph node metastasis of PTC. F-FDG uptake may reflect tumor progression of PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
(40 reference statements)
3
25
2
Order By: Relevance
“…In the initial multivariate analysis, among the various clinicopathologic factors, tumor size and BRAF mutation status were significantly associated with 18 F-FDG avidity. Several studies have shown that the 18 F-FDG uptake of PTCs is significantly associated with tumor size [1][2][3], similar to our study. However, when we performed subgroup analyses in two groups defined by tumor size (< 1 and≥ 1 cm, considering the PET resolution), the BRAF mutation status was the only factor significantly associated with 18 F-FDG avidity in the larger size tumor subgroup (≥ 1 cm), whereas the association between tumor size and avidity was not significant in the two subgroups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the initial multivariate analysis, among the various clinicopathologic factors, tumor size and BRAF mutation status were significantly associated with 18 F-FDG avidity. Several studies have shown that the 18 F-FDG uptake of PTCs is significantly associated with tumor size [1][2][3], similar to our study. However, when we performed subgroup analyses in two groups defined by tumor size (< 1 and≥ 1 cm, considering the PET resolution), the BRAF mutation status was the only factor significantly associated with 18 F-FDG avidity in the larger size tumor subgroup (≥ 1 cm), whereas the association between tumor size and avidity was not significant in the two subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…However, there were also conflicting reports [1][2][3]6] that those parameters are not an independent predictor of 18 F-FDG uptake in PTC, as shown in our study. These results might reflect that the high 18 F-FDG uptake in cancer cells is not necessarily the consequence of rapid proliferation, but is caused by the activation of oncogenic pathways that regulate transporters and enzymes involved in the metabolism of glucose [18].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations